Using LinkedIn - Rutledge, Patrice-Anne (Que Pub., 2010)
Using Linkedin More than just a book Get comfortable with LinkedIn . Don't just read about it: See it and hear it with step-by-step video tutorials and valuable audio sidebars delivered through the Free Web Edition that comes with every USING book. For the price of the book, you get online access anywhere with a web connection--no books to carry, updated content, and the benefit of video and audio learning. Way more than just a book, this is all the help you'll ever need where you want, when you want! learn fast, learn easy, using web, video, and audio Show Me video walks through tasks you've just got to see--including bonus advanced techniques Tell Me More audio delivers practical insights straight from the experts Patrice-Anne Rutledge is a business technology author and consultant who specializes in teaching others to maximize the power of new technologies such as social media and online collaboration. Patrice is a long-time LinkedIn member and social networking advocate who uses LinkedIn to develop her business, find clients, recruit staff, and much more. UNLOCK THE FREE WEB EDITION--To register your USING book, visit quepublishing.com/using. Covers: LinkedIn Category: Internet User Level: Beginner.